Standardized versus customized high-intensity training: effects on cycling performance - Capostagno, B.; Lambert, M. I.; Lamberts, R. P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To determine whether a submaximal cycling test could be used to monitor and prescribe high-intensity interval training (HIT). Methods: Two groups of male cyclists completed 4 HIT sessions over a 2-wk period. The structured-training group (SG; n = 8, VO2max = 58.4 ± 4.2 mL/min·kg) followed a predetermined training program while the flexible-training group (FG; n = 7, VO2max = 53.9 ± 5.0 mL/ min · kg) had the timing of their HIT sessions prescribed based on the data of the Lamberts and Lambert Submaximal Cycle Test (LSCT). Results: Effect-size calculations showed large differences in the improvements in 40-km time-trial performance after the HIT training between SG (8 ± 45 s) and FG (48 ± 42 s). Heart-rate recovery, monitored during the study, tended to increase in FG and remain unchanged in SG. Conclusions: The results of the current study suggest that the LSCT may be a useful tool for coaches to monitor and prescribe HIT.